Synchronous field measurement of high energy sand saltation on typical desert surfaces, Alxa plateau - Yu Gu; Yong Liu; Peijun Shi; Guoming Zhang; Yanyan Yang; Guangpeng Wang; Ziying Hu; Lianyou Liu (Scientific Reports)
Abstract Investigating aeolian saltation over typical desert surfaces is crucial for understanding aeolian patterns and geomorphic development in arid and semi-arid regions. However, ground-based synchronous measurements on various land surfaces are scarce, and usually in limited measurement duration. The Alxa Plateau is characterized by strong wind, extensive wind erosion, and is one of the main dust source areas in China. In this study, we conducted year-long synchronous sand saltation measurements on five typical desert surfaces (gravel Gobi, fine-gravel flat, sand sheet, mud-flat nebkha, and salt-flat nebkha), in the transitional zone between the downstream plain of Heihe River and Badain Jaran Sand Desert. The measurements revealed that, under the local arid climate, the average annual 2 m-high wind speed on gravel Gobi was similar to that on sand sheet, but 1.26 to 1.43 times higher than that on the other three surface types. Sand saltating number on sand sheet was 1 order of magnitude greater than gravel Gobi and 2–3 orders greater than the other surfaces. The majority of sand saltation activities occurred within 10–30℃ air temperature and 10–30% relative humidity. Surface roughness and sand availability might be important factors affecting wind speed and aeolian saltation activity. The majority of sand saltation was chiefly caused by high wind speed and long-duration sand-transporting events. We detected the average particle kinetic energy decreased with increasing wind speed and concentration of saltating sand, implying that enhanced collisions among numerous sand particles at higher wind speeds might substantially reduce the abrasive efficiency of individual sand particles.